Polymorphisms in PI3K/AKT genes and gene‑smoking interaction are associated with susceptibility to tuberculosis - Chunli Wu; Huixia Liu; Ying Lin; Rongjing An; Mian Wang; Hua Zhong; Hengzhong Yi; Qiaozhi Wang; Hongzhuan Tan; Lizhang Chen; Jing Deng; Mengshi Chen (Taylor & Francis Group, 2023)
AbstractBackground Phosphatidylinositol 3-kinase (PI3K) and protein kinase B (AKT) are involved in the clearance of Mycobacterium tuberculosis (MTB) by macrophages.Aim This study aimed to investigate the effects of polymorphisms in the PI3K/AKT genes and the gene-smoking interaction on susceptibility to TB.Methods This case-control study used stratified sampling to randomly select 503 TB patients and 494 control subjects. Logistic regression analysis was used to determine the association between the polymorphisms and TB. Simultaneously, the marginal structure linear dominance model was used to estimate the gene-smoking interaction.Results Genotypes GA (OR 1.562), AA (OR 2.282), and GA + AA (OR 1.650) at rs3730089 of the PI3KR1 gene were significantly associated with the risk to develop TB. Genotypes AG (OR 1.460), GG (OR 2.785), and AG + GG (OR 1.622) at rs1130233 of the AKT1 gene were significantly associated with the risk to develop TB. In addition, the relative excess risk of interaction (RERI) between rs3730089 and smoking was 0.9608 (95% CI: 0.5959, 1.3256, p < 0.05), which suggests a positive interaction.Conclusion We conclude that rs3730089 and rs1130233 are associated with susceptibility to TB, and there was positive interaction between rs3730089 and smoking on susceptibility to TB.